Interrogating the Tailoring Steps of Pactamycin Biosynthesis and Accessing New Pactamycin Analogues. (22nd July 2016) - Abugrain, Mostafa E.; Lu, Wanli; Li, Yuexin; Serrill, Jeffrey D.; Brumsted, Corey J.; Osborn, Andrew R.; Alani, Adam; Ishmael, Jane E.; Kelly, Jane X.; Mahmud, Taifo
Abstract: Pactamycin is a bacteria‐derived aminocyclitol antibiotic with a wide‐range of biological activity. Its chemical structure and potent biological activities have made it an interesting lead compound for drug discovery and development. Despite its unusual chemical structure, many aspects of its formation in nature remain elusive. Using a combination of genetic inactivation and metabolic analysis, we investigated the tailoring processes of pactamycin biosynthesis in Streptomyces pactum . The results provide insights into the sequence of events during the tailoring steps of pactamycin biosynthesis and explain the unusual production of various pactamycin analogues by S. pactum mutants. We also identified two new pactamycin analogues that have better selectivity indexes than pactamycin against malarial parasites. Abstract : Roadblock detour : A combination of genetic inactivation and metabolic analysis in Streptomyces pactum reveals the natural pathway to pactamycin and explains the unusual production of various pactamycin analogues by S. pactum mutants.